Glued to Which Face? Attentional Priority Effect of Female Babyface and Male Mature Face - Zheng, Wenwen; Luo, Ting; Hu, Chuan-Peng; Peng, Kaiping (Frontiers in Psychology, 2018)
A more babyfaced individual is perceived as more child-like and this impression from babyface, as known as babyface effect, has an impact on social life among various age groups. In this study, the influence of babyfaces on visual selective attention was tested by cognitive task, demonstrating that the female babyface and male mature face would draw participants' attention so that they take their eyes off more slowly. In Experiment 1, a detection task was applied to test the influence of babyfaces on visual selective attention. In this experiment, a babyface and a mature face with the same gender were presented simultaneously with a letter on one of them. The reaction time was shorter when the target letter was overlaid with a female babyface or male mature face, suggesting an attention capture effect. To explore how this competition influenced by attentional resources, we conducted Experiment 2 with a spatial cueing paradigm and controlled the attentional resources by cueing validity and inter-stimulus interval. In this task, the female babyface and male mature face prolonged responses to the spatially separated targets under the condition of an invalid and long interval pre-cue. This observation replicated the result of Experiment 1. This indicates that the female babyface and male mature face glued visual selective attention once attentional resources were directed to them. To further investigate the subliminal influence from a babyface, we used continuous flash suppression paradigm in Experiment 3. The results, again, showed the advantage of the female babyfaces and male mature faces: they broke the suppression faster than other faces. Our results provide primary evidence that the female babyfaces and male mature faces can reliably glue the visual selective attention, both supra- and sub- liminally.